EFFECT OF PROGESTERONE AND HCG AFTER ARTIFICIAL INSEMINATION ON PREGNANCY RATES AND PROGESTERONE LEVELS IN BALI TIMOR COWS - Henderiana L.L. Belli; Filemon Y. Lanata; Petrus Kune; Imanuel Benu (JURNAL NUKLEUS PETERNAKAN, 2022)
This study determined whether the administration of progesterone and hCG after insemination increased pregnancy rate in Bali Timor cows. A total of 30 Bali Timor cows (BW ± 200-225 kg; aged 3-7 years old) with different parity were used in this study. Cows were inseminated with progesterone and hCG. Cows were grouped based on body weight and number of parities following a Complete Randomized Design with 3 treatments and 10 replications. The treatments were: P1 = did not receive any treatment (control); P2 = estrus induced by PGF2α 125 mg on day 5, 7 and 9 (n = 10); and P3 = estrus induced by hCG 1000 IU on day 5 after artificial insemination (AI). Blood samples were collected from the jugular vein of the animals on day 0 and continued for a period of 33 days after AI using 5 mL heparinised pre-set syringes Blood samples were then centrifuged at 1500 rpm for 10 minutes. Serum was harvested and stored at -20oC until serum concentrations of progesterone and hCG were determined using ELISA procedures. Pregnancy was determined by rectal palpation. The results showed that the AI pregnancy rates was greater in group treated with hCG (70%) than cows induced with progesterone (50%) or the control group. The concentrations of both progesterone and hCG were increased simultaneously on day 5 to 11 post AI. In conclusion, progesterone and hCG application in Bali Timor cows after artificial insemination could increase pregnancy rates.